MON-LB77 Inhibitors of XIAP as Novel Therapeutic Agents in Thyroid Cancer - Chu, Simon (J Endocr Soc, 2020)
Treatment options for radioiodine-refractory epithelial thyroid cancer (ETC) are limited to tyrosine kinase inhibitors (TKIs), which are associated with significant adverse effects and are not curative. The inhibitors of apoptosis (IAP) family have oncogenic properties and overexpression of X-linked IAP (XIAP) in papillary thyroid carcinoma (PTC) is associated with a poor prognosis. Our group has previously reported a synergistic interaction between SMAC mimetics (SM) (IAP antagonists with XIAP and cIAP1 specificity), and PPARgamma agonists in granulosa cell tumors (1). Such an approach has not been explored in ETC. We hypothesize that SM may be efficacious alone or in combination with a secondary agent to inhibit proliferation, induce cell death and/or promote differentiation to resensitize cells to radioiodine. Four ETC-derived cell lines (K1, Nthy-ori 3-1, TPC-1 and SW-1736) were examined for cIAP1, cIAP2 and XIAP expression by RT-PCR. The K-1 and TPC-1 cell lines (PTC origin, BRAFV600E and PI3KCA mutation positive) were chosen to investigate the effects of an SM in combination with either a PPARgamma agonist (rosiglitazone) or a broad-spectrum TKI (sorafenib). Cell proliferation was examined using xCELLigence Real-Time Cell Analysis. Viability was assessed using total cell counts at 24 and 48 hours. In the four cell lines, we found abundant cIAP1 and XIAP expression and low cIAP2 expression. When an SM was used in combination with either rosiglitazone or sorafenib, we observed significant impairment of cell proliferation and viability with a clear morphological response. These effects appear SM-dependent, as SM treatment alone also showed significant effects on proliferation. However, these effects were enhanced when combined with sorafenib, which was ineffective alone. Markers of differentiation are currently being examined. Our findings suggest a novel role for SM in treating or redifferentiating radioiodine-refractory ETC. Clinically, this may involve lower doses of individual agents than when used alone, thereby reducing adverse effects. References1. Leung, D.T.H., et al., Combined PPARgamma Activation and XIAP Inhibition as a Potential Therapeutic Strategy for Ovarian Granulosa Cell Tumors. Mol Cancer Ther, 2019. 18(2): p. 364-375.